European Council - Bulmer, Simon. author. aut Link
XII, 174 p.
Keywords: Using a wide range of material the authors aim to provide a thorough assessment of the European Council's work from 1975 to 1985. They explain its fluctuating performance, its impact on other European Community institutions and analyze it in the context of international and domestic issues.